Preoperative and Postoperative Resting Energy Expenditure of Patients Undergoing Major Abdominal Operations. Issue 1 (7th April 2020) - Silva, Thales Antônio; Maia, Fernanda de Carvalho Pazzini; Zocrato, Maria Clara Arantes; Mauricio, Silvia Fernandes; Correia, Maria Isabel Toulson Davisson; Generoso, Simone de Vasconcelos
Abstract: Background: Nutrition therapy plays a major role in the perioperative management of surgical patients. Understanding energy metabolism and correctly establishing the adequate energy needs is a crucial step to provide optimal nutrition care. The aim of this study was to assess the resting energy expenditure (REE) after major abdominal procedures and its associated factors. Methods: This was a prospective observational study conducted at a single center. REEs of patients admitted for gastrointestinal surgical procedures were measured by indirect calorimetry 24 hours prior to the procedure and reassessed at least once within the fifth postoperative day. Substrate oxidation was calculated according to the Frayn equation. Nutrition status was evaluated using subjective global assessment. Results: There were no significant changes in the REEs throughout the study period; however, there was a decrease in the respiratory quotient during the postoperative period, as well as a decrease in carbohydrate oxidation and an increase in lipid oxidation. Only 33.3% of the patients presented a postoperative increase in REE > 10%. Those patients presented higher blood‐monocyte levels. Conclusion: Postoperative REE is not increased in most of the patients. In patients who had increased REE, associated factors included higher levels of monocytes.